Humanist Character Education As An Anti-District Effortbullying At The Boarding School - Achmad Anwaruddin; M. Muizuddin (Jurnal Multidisiplin Indonesia, 2026)
Abstract. This study stems from the increasing number of bullying cases in educational institutions, including Islamic boarding schools, which shows a gap between the ideal of character education and the reality of violence. The main question of this study is how humanistic character education can be formulated as a preventive anti-bullying model in Islamic boarding schools. This study positions itself as an integrative conceptual study that connects institutional approaches and individual spiritual dimensions within the framework of educational humanism. The method used is a literature study with a descriptive-analytical approach through the stages of identification, selection, thematic classification, and content analysis of relevant literature. The results of the study show that a humanistic character education model that integrates the values of religiosity, empathy, respect for human dignity, justice, responsibility, and independence, and is implemented through dialogical pedagogy, educator role modeling, institutional policy support, and the transformation of ukhuwah culture, has the potential to strengthen the internalization of values in a substantive manner and prevent systemic bullying practices. This model offers a comprehensive preventive framework that not only suppresses aggressive behavior but also builds a safe, inclusive, and civilized educational environment.